Kualitas Minyak Urut Kombinasi VCO dan Cabai Jawa (Piper retrofractum Vahl.) dengan Variasi Suhu Pemanasan pada Proses Digesti - Dewa Ayu Ika Pramitha; Ni Wayan Rias Samidya; Luh Dita Sukriani; Maria Malida Vernandes Sasadara; Agung Ari Chandra Wibawa (Jurnal Ilmiah Medicamento, 2023)
The alternative to increasing VCO's functional value is adding spices that contain functional components. In this study, an analysis of the quality of the massage oil preparation of the combination of VCO Piper retrofractum was carried out using heating temperatures of 40°C, 50°C, and 60°C in the digestion process for 8 hours and macerated for 24 hours. The purpose of this study was to determine the best temperature that can be used in the process of making Javanese chili VCO massage oil which has the best quality. The quality parameters determined were water content, acid number, peroxide number, and iodine number. The massage oil is orange and has a distinctive Javanese chili aroma. The results of the analysis of the processed oil produced show that massage oil at 40°C has a water content, acid number, peroxide value, and iodine number of (0.018 ± 0.008) %; (1.185 ± 0.072) mg NaOH/10g; (0.433 ± 0.058) meq/kg; and (7.358 ± 0.032) g iodine/100 g oil. Thus, the best quality is produced by massage oil, which is processed using a temperature of 40°C. It has the lowest water content, acid number, peroxide number, and highest iodine number compared to those obtained at higher heating.